Thought revolution through bhav samvedana: In the view of pt. shriram sharma acharya - MEGHA PAL (Dr. Chinmay Pandya, 2013)
God has bestowed the highest level of consciousness and emotional stimulations to a human being. But nowadays human being is continuously working against his dignity; so the humanity appears beyond redemption. If this state of affairs continues, men and society would suffer irrecoverable regression. Humanity will have to pay a heavier price for the so called progress. In spite of best efforts, the top talents and elites of the world have not found solutions to the problems. Pt. Shriram Sharma Acharya worked a lot on the problems of present era and after that he found that the root cause of all problems is the 'Vikriti' (degeneration) of 'Bhav Samvedana' (emotional sensitivity). To begin with, one has to get rid of all kinds of negativities in one's emotions so that 'Bhav Samvedana' can be evoked. 'Bhav Samvedana' is the greatest boon of God to a human being. When the level of inner being will change, thoughts and actions would automatically work in an excellent manner. The chief motive of his life and sayings is to evoke 'Bhav Samvedana' by creating a positive change in our lives, life styles, attitude and moral values, etc. As much as 'Bhav Samvedana' works in a higher manner, it would initially illuminate our mind and thoughts. As a result, 'Bhav Samvedana' would cause thought revolution and this would refine our consciousness that is called- Human Excellence.